Modeling of Solid State Detectors Using Advanced Multi-Threading: The TCoDe and TFBoost Simulation Packages - Brundu, D.; Contu, A.; Cossu, G. M.; Loi, A. (Frontiers in Physics, 2022)
Particle tracking for future experiments at colliders is an incredible challenge in terms of sensor technology and readout. Simulation tools are a crucial ingredient to investigate new layouts able to cope with harsh radiation conditions and, at the same time, provide valuable timing information for track finding algorithms. Detailed and numerous simulations of energy deposits as well as sensor and front-end electronics responses imply a heavy usage of computing resources. In this paper, we present two software packages that, via massive parallelization and dedicated algorithms, allow for a significant speed-up in simulation time.